Pengaruh Human Resource Management Practices and Policies, Transformational Leadership Style Terhadap Job Satisfaction: Studi Pada PT. X - Subroto, Ruri Hudi Astuti Dewi (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2021)
Human resource development programs need to be created systematically and sustainably to produce future-ready talents. As part of the efforts to optimize human resources management within the company, one of the ways the company takes is by increasing employee satisfaction in carrying out its duties. The purpose of this study was to determine the effect of human resource management practices and policies, transformational leadership style on job satisfaction. This research method uses a quantitative approach. The sample in this study were 235 employees of PT. X. The type of data used is primary data using a questionnaire. The analysis technique used is Structural Equation Modeling with AMOS 22 program tools. The results of this study are expected to be used as an evaluation material for human resource management practices and policies that have been implemented by the company, in order to make improvements to aspects that are still complaints and make employees feel dissatisfied when working such as job placements that aren’t according to capacity, the balance of the weight of the work given, the assessment system to the problem of the compensation system or its achievement which aims to create job satisfaction and employee comfort at work.